Epidemiology of Organophosphate Poisoning in the Tshwane District of South Africa - LL Razwiedani; PGD Rautenbach (SAGE Publishing, 2017)
Background: Organophosphate poisoning is a major public health problem in South Africa. Individuals get exposed to organophosphate in both the domestic and industrial spheres. Method: A cross-sectional study was conducted using retrospective, secondary data of organophosphate poisoning cases over a 3-year period, reported at the Tshwane District surveillance office. Data were analysed using Microsoft Excel, and Epi Info version 7 was used for descriptive statistics. Results: A total of 207 cases were reported with ages ranging from 10 months to 59 years. Most of the cases were men (58.9%). Intentional poisoning accounted for 51% of cases. Unintentional poisoning accounted for 21.7% of cases, and 26.5% of cases had unknown circumstances of poisoning. A significant number (50.2%) of intentional poisonings were suicide related. Nonsuicidal cases accounted for 47.4% of cases, and deliberate unlawful poisoning accounted for 2.4% of cases. The mortality rate for the whole group was 3.4%. Conclusions: Improvement in data collection on organophosphate poisoning is essential to properly measure the burden of the problem. More effective regulatory controls for pesticide use are needed in South Africa.